The Environmental Impact Assessment of the Spent Engine Oil Recycling Plant by using Leopold Matrix: Case Study Recycling Plant in Al-Diwaniyah City – Iraq - Mohammed K. Alkasser; Mukhtar D. Abbas (Al-Qadisiyah Journal of Pure Science, 2021)
The study achieve to make an environmental impact assessment for a spent engine oil recycling plant in AL-Diwaniyah city – Iraq. The assessment has been carried out using Leopold matrix. The studied plant deals with the bentonite clay as adsorbent material for removing the impurities from spent oil. The waste of bentonite clay which has been discharged as by- product waste without any minimal level of remediation which is harmful to the all environmental components in addition to that, the plant discharges air pollutants during the operation.Leopold matrix is a simple method in terms of applying and using, it can be used easily for a comparison among different projects and gives clarified results. Moreover, the significant characteristic is its ability to covering biological, physical, economic and social environment. From the results of Leopold matrix analysis, it can be observed that the maximum impact of the plant was on physical components in both quantity and importance, while there are some positive impacts on social components. Generally, all the impacts that caused from the plant is low on the environment by the comparison with maximum locally index of environmental impact value.